Salvinia natans microplate assay: A simple and efficient method for evaluating aquatic toxicity. (December 2022) - Cui, Rongxue; Kwak, Jin Il; An, Youn-Joo
Abstract: This study proposes a microplate assay for chemical toxicity evaluation using S. natans ; this assay is a miniaturization of a culture dish assay from previous studies. The optimal initial frond number of S. natans in the microplate assay was established and the feasibility of the microplate assay was evaluated. To evaluate the applicability of the developed method, S. natans was exposed to six model chemicals (one metalloid and five heavy metals) and the specific growth rate and photosynthetic activity were compared. We determined that the optimal initial frond number was four fronds for the microplate assay. Additionally, toxicity sensitivity to six model chemicals revealed similar results to the culture dish assay. Therefore, we propose that the S. natans microplate assay is a simple and effective method to assess ecotoxicity as it requires less test solution and area than the culture dish assay. This methodology can be expandable to ecotoxicological research. Highlights: Salvinia natans is an effective test species for assessing chemical toxicity. We developed an effective microplate assay for chemical toxicity using S. natans . The microplate assay is superior to the culture dish assay. Frond number and area of S. natans decrease under metal and metalloid stress. Four is the optimal number of fronds for the S. natans microplate assay.